IMPLEMENTATION OF A CREATIVE WRITING TEXTBOOK BASED ON LOCAL WISDOM FOR PBI UNS STUDENTS IN WRITING POETRY - Sri Hastuti (2024)
Learning to write poetry will run well if it is supported by appropriate teaching materials. There are no conditions for using creative writing textbooks that specifically discuss writing poetry that focuses on local wisdom. This research aims to determine the implementation of the Creative Writing textbook based on Local Wisdom for Indonesian Language Education students in writing poetry. The research method used is quantitative to present the findings based on the use of a Creative Writing textbook based on Local Wisdom. The technique in testing effectiveness uses paired samples t-test. The findings of this research are the effectiveness of learning to write poetry using creative writing textbooks based on local wisdom